Pelatihan Pemanfaatan Media Pembelajaran Interaktif Menggunakan Articulate Storyline 3 dalam Pembelajaran Blended Learning - Bunyamin, Bunyamin; Arifin Rahmanto, Muhammad (Jurnal SOLMA, 2022)
Background: The limited PTMT policy says teachers must have innovations in learning. PPT at SMP Muhammadiyah 9 Jakarta is considered ineffective in blended learning activities. Therefore, training was held in the use of the Articulate Storyline 3 application to be used as an interactive learning medium. To improve the professional ability of teachers in making technology-based learning media. Method: Survey method to find out and analyze the results of the questionnaire instruments provided related to training materials and the delivery of resource persons. A total of 33 participants participated in an online zoom meeting held at SMP Muhammadiyah 9 Jakarta. Results: Teachers can have innovations in making engaging learning media, teachers can make the material as creative as possible, using audiovisual and supporting images, and teachers are interested in using this storyline in three articulate applications in the learning process. Conclusion: This training activity helps teachers learn innovation, and there is a positive interest in Articulate Storyline 3.